Metacognitive deficits in frontotemporal dementia. Issue 12 (16th November 2005) - Eslinger, P J; Dennis, K; Moore, P; Antani, S; Hauck, R; Grossman, M
Abstract : Objectives: To investigate whether metacognitive impairments in self-awareness and self-monitoring occur in patients with frontotemporal dementia (FTD), particularly among those with prominent social and dysexecutive impairments. Methods: Patients diagnosed with FTD were divided by clinical subtype (social–dysexecutive (n = 12) aphasic (n = 15), and constituent subgroups of progressive non-fluent aphasia and semantic dementia) and compared with subjects with probable Alzheimer's disease (AD, n = 11) and age-matched healthy controls (n = 11). All subjects completed comprehensive behavioural ratings scales, which were compared with caregiver ratings. Subjects also rated their test performances in verbal associative fluency, word list learning, and memory task with comparisons made between actual and judged performance levels. Results: The FTD sample as a whole showed significantly less behavioural self-awareness and self-knowledge than the AD and healthy control samples. FTD patients with prominent social and dysexecutive impairments demonstrated the most extensive loss of self-awareness and self-knowledge, significantly overrating themselves in multiple social, emotional, and cognitive domains, and failing to acknowledge that any behavioural change had occurred in most areas. The remaining clinical samples showed select and minimal discrepancies. All clinical groups were significantly unaware of their apathy levels. Most FTD patients judged episodic cognitive test performance adequately, with partial difficulties observed in the socially impaired and progressive non-fluent aphasia subgroups. Conclusions: FTD patients, particularly those with prominent social and dysexecutive impairments, exhibit profound metacognitive anosognosia that may represent a loss of self-awareness, self-monitoring, and self-knowledge, likely related to significant prefrontal pathophysiology. Other FTD clinical groups and AD patients showed less pervasive and more select metacognitive deficiencies.